1994
DOI: 10.1021/np50114a002
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopsychotride A, a Biologically Active, 31-Residue Cyclic Peptide Isolated from Psychotria longipes

Abstract: A preliminary characterization is provided of a naturally occurring cyclic peptide with interesting and potent biological activity. A 31-residue cyclic peptide, designated cyclopsychotride A [1], was obtained from the organic extract of the tropical plant, Psychotria longipes. Compound 1 inhibited [125I] neurotensin (NT) binding to HT-29 cell membranes (IC50 3 microM) and also stimulated increased levels of cytosolic Ca2+ in two unrelated cell lines that do not express NT receptors. The peptide was found to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
246
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(249 citation statements)
references
References 4 publications
2
246
0
1
Order By: Relevance
“…Of particular interest among naturally occurring examples have been a series of plant-derived proteins referred to as the cyclotides (1). These include kalata B1 (2), the circulins (3), cyclopsychotride (4), and several peptides from Viola species (5-7). The cyclotides comprise 29-31 amino acids, including six highly conserved Cys residues that form a cystine knot (8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest among naturally occurring examples have been a series of plant-derived proteins referred to as the cyclotides (1). These include kalata B1 (2), the circulins (3), cyclopsychotride (4), and several peptides from Viola species (5-7). The cyclotides comprise 29-31 amino acids, including six highly conserved Cys residues that form a cystine knot (8)(9).…”
mentioning
confidence: 99%
“…For example, in 1970, kalata B1was reported as the active ingredient in a tea used by women in the Congo region of Africa to accelerate childbirth (16,17), although it was some 25 years later before the sequence and cyclic nature of the peptide were determined (2). The circulins were discovered in screens focusing on anti-HIV activity (3), cyclopsychotride for inhibition of neurotensin binding (4), and various Viola peptides for hemolytic activity (7). Thus, all of the known macrocyclic peptides have diverse biological activities, but their function in plants was not known.…”
mentioning
confidence: 99%
“…[4] It is believed that the compact CCK motif of cyclotides is responsible for their exceptional resistance against chemical, thermal, and proteolytic degradation. [5] Cyclotides display a diverse range of biological activities, including uterotonic, [6] haemolytic, [7][8][9] neurotensin antagonistic, [10] HIV inhibitory, [11] antimicrobial, [12] cytotoxic, [13] antifouling, [14] and trypsin inhibitory activities. [15] In addition, kalata B1 and B2 have been shown to inhibit the growth and development of Helicoverpa punctigera and H. armigera larvae, suggesting that cyclotides function as insecticidal agents as part of plant defence systems.…”
mentioning
confidence: 99%
“…These peptides display an interesting range of biological activities, which led to their initial discovery. The circulins were found in a screen for anti-human immunodeficiency virus activity (8), cyclopsychotride A inhibits neurotensin binding to cell membranes (9), and kalata B1 shows uterotonic activity (6,10). Violapeptide I (11) was originally discovered based on its hemolytic activity, and it has recently been shown that kalata B1 (12,13), the circulins (12,13), and cyclopsychotride A (13) also have relatively weak hemolytic activity.…”
mentioning
confidence: 99%